2018
DOI: 10.12738/estp.2018.3.0108
|View full text |Cite
|
Sign up to set email alerts
|

Does Mastery of Goal Components Mediate the Relationship between Metacognition and Mathematical Modelling Competency?

Abstract: Prior studies suggested close correlations among metacognition, mastery goal, and mathematical modelling competency. The present study examines the relationship between metacognition and mastery goal that may influence mathematical modelling competency. The current study employs 538 students of a mathematics education program; among these students, 483 (89.8%) are males and 55 (10.2%) are females, aged from 18 to 22 years old. The study follows a correlational research design to investigate and measure the deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 78 publications
(113 reference statements)
1
4
0
Order By: Relevance
“…The self-approach goal was found to have no effects on both learning interests and mathematics performances, which is consistent with the expectations and arguments of the present study. These results are partially consistent with former studies that found no effects of the self-approach goal on exam performance ( Elliot et al, 2011 ; Gillet et al, 2015 ; Hoi, 2016 ), but they contradict others studies claiming it has a positive effect on mathematics ability ( Hidayat et al, 2018 ). This may be due to different foci among the self-approach goal, two learning interests, and mathematics performances.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The self-approach goal was found to have no effects on both learning interests and mathematics performances, which is consistent with the expectations and arguments of the present study. These results are partially consistent with former studies that found no effects of the self-approach goal on exam performance ( Elliot et al, 2011 ; Gillet et al, 2015 ; Hoi, 2016 ), but they contradict others studies claiming it has a positive effect on mathematics ability ( Hidayat et al, 2018 ). This may be due to different foci among the self-approach goal, two learning interests, and mathematics performances.…”
Section: Discussionsupporting
confidence: 90%
“…Many studies have favored the 3 × 2 achievement goal model across countries and subject domains ( Wu, 2014 ; Gillet et al, 2015 ; Hoi, 2016 ; Mascret et al, 2017 ; Méndez-Giménez et al, 2017 , 2018 ; Wang et al, 2017 ; Hidayat et al, 2018 ; Danthony et al, 2020 ; Hunsu et al, 2021 ). However, this model has mainly been applied to school-aged samples, the exception being Wu (2022b) , who developed an instrument to measure kindergarteners’ achievement goals based on the 3 × 2 achievement goal framework, and this model as preliminarily demonstrated to be the best theoretical model for understanding kindergarteners’ achievement goals.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations